2002
DOI: 10.1037/0735-7036.116.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responsiveness to infant Norway rat ( Rattus norvegicus) ultrasonic vocalizations during the maternal behavior cycle and after steroid and experiential induction regimens.

Abstract: When removed from the nest and placed in a cool environment, Norway rat (Rattus norvegicus) pups emit ultrasonic vocalizations that can elicit maternal search behavior. The authors examined the behavior of pregnant dams, mothers, and virgin females during exposure to a pup that was either warm and silent or cool and vocalizing. Results indicate potentiated maternal reactions to a vocalizing pup: Mothers approached and maintained proximal orientation to a vocalizing pup far more than did virgin females. Elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…This study showed that a warm, silent pup together with recorded ultrasounds was required to elicit approach of maternal or virgin females, the former remaining in proximity of the pup for a significantly longer period of time. A subsequent experiment [26] demonstrated that odors from the pup were important in a mother seeking a pup and maintaining close proximity. Thus, based on these experiments, the pup cries were insufficient, by themselves, to elicit parental behavior in mothers but did appear to activate the initial seeking behavior.…”
Section: Crying and Parental Behaviormentioning
confidence: 98%
“…This study showed that a warm, silent pup together with recorded ultrasounds was required to elicit approach of maternal or virgin females, the former remaining in proximity of the pup for a significantly longer period of time. A subsequent experiment [26] demonstrated that odors from the pup were important in a mother seeking a pup and maintaining close proximity. Thus, based on these experiments, the pup cries were insufficient, by themselves, to elicit parental behavior in mothers but did appear to activate the initial seeking behavior.…”
Section: Crying and Parental Behaviormentioning
confidence: 98%
“…Parallel to human infant cries, neonatal vocalizations are an important offspring cue facilitating early interactions between dam and rodent pup offspring [1214], with sustained high-rate ultrasonic vocalizations (USVs) emitted by pups being the most effective for eliciting retrieval from dams [1518]. Studies also suggest that frequency modulation [19;20] and amplitude of USVs [21] may be important acoustic cues for maternal approach and response.…”
Section: Introductionmentioning
confidence: 99%
“…A number of cues produced by infants can modify maternal responses, including ultrasonic vocalizations (USVs) (Smotherman et al, 1974; Brunelli et al, 1994; Farrell and Alberts, 2002a,b; D'Amato et al, 2005; Okabe et al, 2013), odors (Lévy et al, 2004; Okabe et al, 2013), and temperature (Henning and Romano, 1982; Bates et al, 1985; Leon et al, 1985; Adels and Leon, 1986; Woodside and Jans, 1988; Jans and Woodside, 1990; Stern and Lonstein, 1996). The importance of each cue depends to varying extents on the maternal environment, age of the pup producing the cue, and numerous other factors (Champagne et al, 2001, 2003; Mattson et al, 2001; Brudzynski, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pup-produced cues likely interact with alterations in maternal perception and response resulting from drug exposure or environmental disruption. As a stimulus for maternal attention, a sustained high-rate of vocalizing by pups is the most effective for eliciting retrieval from dams (Deviterne et al, 1990; Brunelli et al, 1994; Farrell and Alberts, 2002a,b; Zimmerberg et al, 2003; Fu et al, 2007) and can also be an important stimulus for licking (Brouette-Lahlou et al, 1992), an important social behavior. Rats of various ages vocalize in response to handling, cold temperatures, isolation, and social factors (Blumberg et al, 1992; Shair et al, 1997; Branchi et al, 2001; Hahn and Lavooy, 2005); thus, USVs constitute one avenue of communication between pup and mother (Brunelli et al, 1994; Brudzynski, 2005).…”
Section: Introductionmentioning
confidence: 99%